Development of Synthetic Variety of Coconut: PCA Syn Var 001 I. Status and Prospects - Ramon L. Rivera; Gerardo A. Santos; Susan M. Rivera; Ernesto. E. Emmanuel (International Coconut Community, 2008)
Increased genotypic heterozygozity through phenotypic disassortative mating improves vigor and yield performance of progenies, while inbreeding causes depression, thus the use of F2 seeds from F1 variety hybrids could lead to disastrous results. Knowing the partiality of coconut farmers in using seeds from any high yielding variety for successive cropping, the development of an open-pollinated variety or OPV with a high degree of balanced heterozygozity is highly desired. Started way back in 1979, the PCA pioneered the development of a synthetic coconut variety, i.e., PCA SYN VAR 001. With some modifications of the classical breeding method, a scheme was formulated to produce the base population of a synthetic coconut variety using single crosses from six tall coconut cultivars, four local and two foreign tall varieties, which were found to possess good general combining ability (GCA). Field planting of the F1 base populations was done in September 1992. Since then, observations on growth and development, flowering and early yield of the genetic materials, as well as the distributions of “bulked” seeds from the plantation are ongoing. The use of modern molecular marker tools, i.e. microsatellite or Simple Sequence Repeat (SSR) marker technology in the development of the synthetic variety of coconut, including the status of the research undertakings and prospects of the new breeding populations are described in this paper.